Developing the Auxiliary Dictionary for the Book of Modern Dialogue with the Pronunciational System on the Special Alphabetical Basis for Middle Class Students at the Institute of Dar Al-Muttaqin Jombang - Mochamad Fawaidur Rochman; Afif Kholisun Nashoih (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Arabic learning at PP. Darul Muttaqin Jombang is not considered optimal, because there is no supporting media in the learning process. Based on the results of observations and interviews, students find it difficult to understand the material in the book Al-Muhawarah Al-Hadithah and are unable to find the meaning of vocabulary in the book using a derivation dictionary. In addition, they include students who have just learned Arabic in the Islamic boarding school, therefore they need a dictionary as a supporting medium in the learning process. The purpose of this study is to find out how the development of the Al-Muhawarah Al-Hadithah Dictionary of Assistance by using an articulation system and sorted according to the letters alfabait khash for wustho class students in PP. Darul Muttaqin Jombang and looked for the effectiveness of the dictionary in learning Arabic. This study uses the ADDIE model development (RD) method. Data collection techniques were carried out by observation, interviews and tests. The validation results from material experts reached 93% and from design experts 84% it showed at a very good level in using the assistive dictionary for the Arabic learning process. Based on the results of the test (T) with Paired Sample T Test through the SPSS 16.0 application. It is known that the T Test value reaches 31.55 and the T Table reaches 2.055, this shows that the value of T Test T Table. Then the hypothesis (H0) is rejected and (H1) is accepted, from these results it can be concluded that the use of the auxiliary dictionary is effective in the Arabic language learning process.